2016
DOI: 10.1007/s00420-016-1148-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in DNA methylation over the growing season differ between North Carolina farmworkers and non-farmworkers

Abstract: Purpose The occupational risk to farmworkers, particularly chronic exposure to pesticides, is an acknowledged environmental and work-related health problem. Epigenetics has recently been shown to contribute to a number of complex diseases and traits, including measures of cognitive function and preclinical neurodegenerative disease. We sought to determine if changes in DNA methylation existed between farmworker and non-farmworker populations, and to identify the genes most likely involved in those changes. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The authors for the first time analysed gene-specific, genome-wide DNA methylation in subjects occupationally exposed to pesticides, and their results suggest that there is a single epigenetic profile in farmworkers over the growing season, compared to non-farmworkers. A variety of 72 genes may be involved, supporting the hypothesis that alterations in DNA methylation may affect several biologicalpathways and potential disease development (63). …”
Section: Epigeneticsmentioning
confidence: 72%
“…The authors for the first time analysed gene-specific, genome-wide DNA methylation in subjects occupationally exposed to pesticides, and their results suggest that there is a single epigenetic profile in farmworkers over the growing season, compared to non-farmworkers. A variety of 72 genes may be involved, supporting the hypothesis that alterations in DNA methylation may affect several biologicalpathways and potential disease development (63). …”
Section: Epigeneticsmentioning
confidence: 72%
“…This could be particularly important among populations known to experience higher and more chronic levels of exposure to pesticides, such as military and minority populations [12,22,32]. DNA methylation alterations are found in the sperm of agricultural workers [27], another population known to experience higher levels of pesticides exposure. These epigenetic biomarkers associated with disease among ancestrally exposed populations will potentially provide a crucial tool for assessing the health effects in later life for the current generation and the health prospects for future generations.…”
Section: Discussionmentioning
confidence: 99%
“…The direct exposure to pesticides is more prevalent among some populations, particularly agricultural laborers. Among such a population, increased methylation in or near 72 genes was found as a result of exposure to pesticides, mostly involving immune response genes [27]. Prenatal exposure to persistent pollutants yields hypomethylation in fetal blood [28].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, published data have described changes in DNA methylation by pesticide exposure. However, no studies have been conducted concerning the WRAP53 methylation in a population exposed to environmental pollutants. Indeed, the information related to humans exposed to pesticides and epigenetic modifications is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have evaluated gene-specific DNA methylation in populations exposed to pesticides. ,,, Specifically, Howard et al identified changes in DNA methylation at 36 CpG sites, located in or near to 72 genes, in farmworkers compared with nonfarmworkers. Lee et al observed a hypomethylation in the Alu assay for men and global DNA hypermethylation in LINE-1 for women in a population exposed to persistent organic pollutant, including organochlorine pesticides.…”
Section: Discussionmentioning
confidence: 99%